2017
DOI: 10.1007/s10439-017-1817-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin in Reproductive Tissue Engineering: A Review on Its Application as a Biomaterial for Fertility Preservation

Abstract: In recent years, reproductive medicine has made good use of tissue engineering and regenerative medicine techniques to develop alternatives to restore fertility in cancer patients. For young female cancer patients who cannot undergo any of the currently applied strategies due to the possible presence of malignant cells in their ovaries, the challenge is creating an in vitro or in vivo artificial ovary using carefully selected biomaterials. Thanks to its numerous qualities, fibrin has been widely used as a scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 80 publications
0
48
0
Order By: Relevance
“…Stem cells can be derived from different sources; however, different types of stem cells are still hard to gain. Preclinical studies have reported that transplantation of stem cells into POF animal models restored ovarian function and generated immature oocytes (Chiti, Dolmans, Donnez, & Amorim, 2017).…”
Section: Tissue Engineering and Pofmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells can be derived from different sources; however, different types of stem cells are still hard to gain. Preclinical studies have reported that transplantation of stem cells into POF animal models restored ovarian function and generated immature oocytes (Chiti, Dolmans, Donnez, & Amorim, 2017).…”
Section: Tissue Engineering and Pofmentioning
confidence: 99%
“…Reproductive technology has been recently used in tissue engineering and regenerative medicine techniques to restore POF-related infertility by overcoming the donor supply limitations and immune system complications for tissue transplantation (Chiti et al, 2017;Volkova, Yukhta, & Goltsev, 2017).…”
Section: Tissue Engineering and Pofmentioning
confidence: 99%
“…It releases steroid hormones after puberty and thereby fosters follicular development and periodic oocyte release (Y. J. Kim et al, ; Y. J. Kim, Ku, Rosenwaks et al, ; Y. J. Kim, K. E. Park et al, ). Ideally and anatomically, the artificial ovary needs to contain follicles isolated from cryopreserved ovarian tissue and possibly other ovarian cells to provide growth factors (Chiti et al, ). It also requires a proper delivery scaffold that is biocompatible, minimally inflammatory, suitable for neo‐angiogenesis, and degradable after engraftment for not to disturb follicular growth and migration (Amorim & Shikanov, ).…”
Section: Theoretical Overview Of the Artificial Ovarymentioning
confidence: 99%
“…Many researchers have described the essential components and characteristics of the artificial ovary. A group of investigators maintained that the artificial ovary refers to “a temporary surrogate of the natural ovary in which isolated follicles, ovarian stromal cells and a combination of growth factors can be encapsulated together inside a biomaterial‐based scaffold” (Chiti, Dolmans, Donnez, & Amorim, ). Another group suggested that the artificial ovary contain isolated follicles in a biomaterial and thus is able to preserve fertility and replace hormonal functions of the ovary with a significantly decreased risk of introducing malignant cells back into patients (Soares et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop a suitable supporting matrix for human isolated follicles, different polymers have been used in our in vivo studies (Dolmans et al, 2007;Paulini et al, 2016;Chiti et al, 2018). Among all these studies, fibrin formulations with high concentrations of fibrinogen and thrombin were found to be the best choice for supporting follicle survival after xenotransplantation (Paulini et al, 2016;Chiti et al, 2017aChiti et al, , 2018. This is probably because their ultrastructure and rigidity resemble the human ovarian cortex (Paulini et al, 2016;Chiti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%